Composite material for cable shielding layer film and preparation method thereof

By using metallocene linear low-density polyethylene and other high-performance polymers in the cable shielding film materials, combined with twin-screw granulation technology, the problems of insufficient tensile strength, yield strength and water vapor barrier properties of existing materials are solved, and higher mechanical properties and better water vapor barrier effects are achieved, extending the service life of the cable.

CN119570146AActive Publication Date: 2025-03-07NIFLON MACROMOLECULAR MATERIAL (SH) CO LTD

Patent Information

Application Number
CN202411911692.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-07
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The tensile strength and yield strength of the existing cable shielding film materials are insufficient, resulting in peeling between the metal strip and the plastic film layer, and insufficient water barrier performance, which cannot meet the warranty requirements for long-term use.

Method used

The composite material is used with metallocene linear low-density polyethylene as the matrix, and the polychlorotrifluoroethylene, ethylene chloride trifluoroethylene copolymer and ethylene tetrafluoroethylene are added to prepare the composite material through twin-screw granulation technology to improve its tensile strength, yield strength and water vapor barrier properties.

Benefits of technology

It significantly improves the tensile strength and yield strength of the composite material, enhances the water vapor barrier performance, extends the service life, effectively protects the metal belt and meets the warranty requirements for long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205839710000051
    Figure BDA0005205839710000051
  • Figure BDA0005205839710000061
    Figure BDA0005205839710000061
  • Figure BDA0005205839710000062
    Figure BDA0005205839710000062
Patent Text Reader

Abstract

The invention discloses a composite material for a cable shielding layer film and a preparation method of the composite material. A resin matrix of the composite material comprises 30-60 parts by mass of metallocene linear low density polyethylene, 3-10 parts by mass of an ethylene-octylene copolymer, 3-20 parts by mass of polytrifluorochloroethylene, 3-10 parts by mass of an ethylene trifluorochloroethylene copolymer and 15-40 parts by mass of an ethylene tetrafluoroethylene copolymer, and the total parts by mass of the resin matrix is 100. The tensile strength of the composite material for the cable shielding layer film is larger than 40 MPA, and the composite material is not prone to stripping from a metal belt; the yield strength is greater than 10MPA, and the steel is not easy to be stretched and deformed in the compounding process of the steel and a metal belt; the water vapor transmission rate is smaller than 6, the water vapor barrier effect is good, hydrolysis is not prone to occurring, aging resistance is good, the metal belt can be well protected within the quality guarantee period, and in addition, the flame retardant property is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable shielding layer films, and in particular to a composite material for cable shielding layer films and a preparation method thereof. Background Art

[0002] Metal composite tape is a common shielding material in the cable industry. It is made of metal tape, plastic film, and glue through semi-dry gluing and processing. It is coated on the outside of the insulation layer to play the role of electromagnetic shielding. The function of the metal composite tape is determined by the characteristics of the materials that make up its layers. Among them, the metal layer should have excellent shielding performance, mechanical properties, corrosion resistance, etc., mainly aluminum tape, stainless steel tape and copper tape; and the plastic film layer is generally a polyethylene or ethylene copolymer resin material with excellent mechanical properties, strong adhesion to the metal tape, and high heat sealing strength. In recent years, through the development of technology in the corresponding field, the plastic film layer material has developed from the original single polyethylene film and EAA film to a multi-layer structure film of EAA, PE, and PET.

[0003] The metal composite tape has excellent shielding performance. Its barrier performance can prevent the wire core from getting wet. The film layer structure also provides good corrosion resistance to protect the internal wire core and metal tape. However, due to the insufficient tensile strength of the film material, the metal tape and the plastic film layer peel off. At the same time, due to the low yield strength, the film is easily stretched and deformed during the composite process of the metal tape and the film. The insufficient water barrier performance of polyethylene and the aging of the internal metal layer caused by the hydrolysis resistance of PET cannot meet the quality requirements of the cable material with a warranty period of 30 years. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a composite material for cable shielding layer membrane and a preparation method thereof, which can achieve that the film material has excellent tensile strength and high yield strength, and at the same time has the characteristics of good water vapor barrier, excellent flame retardancy, high temperature resistance and aging resistance.

[0005] In order to solve the above technical problems, the first aspect of the present invention is to provide a composite material for cable shielding layer film.

[0006] The resin matrix includes the following components in parts by mass:

[0007] 30-60 parts by weight of metallocene linear low-density polyethylene;

[0008] 3-10 parts by mass of ethylene-octene copolymer;

[0009] 3-20 parts by mass of polychlorotrifluoroethylene;

[0010] 3-10 parts by weight of ethylene chlorotrifluoroethylene copolymer;

[0011] 15-40 parts by weight of ethylene tetrafluoroethylene copolymer;

[0012] The resin matrix has a total of 100 parts by mass;

[0013] The composite material also includes the following components in parts by mass:

[0014] 3-8 parts by mass of compatibilizer;

[0015] 8-18 parts by mass of magnesium hydroxide;

[0016] 0.2-1 parts by mass of silicon dioxide;

[0017] 3-15 parts by mass of montmorillonite;

[0018] Silane coupling agent 0.3-1 parts by mass;

[0019] Dispersant 0.1-1 parts by mass;

[0020] Antioxidant 0.1-1 parts by weight.

[0021] In the present invention, polychlorotrifluoroethylene (PCTFE), ethylenechlorotrifluoroethylene copolymer (ECTFE) and ethylenetetrafluoroethylene copolymer (ETFE) are added to a matrix of metallocene linear low-density polyethylene (MLLDPE) and ethylene-octene copolymer (POE), thereby greatly improving the mechanical properties of the composite material, such as tensile strength and yield strength, and effectively improving the water vapor barrier property of the composite material. In particular, ETFE is mainly used to improve the mechanical properties of the composite material, PCTFE is mainly used to improve the water vapor barrier effect of the composite material, and ECTFE is mainly used to enhance the compatibility between ETFE and PCTFE.

[0022] In the present invention, montmorillonite is a trialkyl quaternary ammonium modified layered silicate, which mainly plays a role in further improving the water vapor barrier effect; silicon dioxide mainly plays a role of a nucleating agent, and has a certain reinforcing effect, thereby improving the strength of the product; the compatibilizer is preferably maleic anhydride grafted metallocene polyethylene; the silane coupling agent is one or more of a triethoxysilane coupling agent and a fluorine-containing silane coupling agent (heptadecafluorodecyltrimethoxysilane); the dispersant is EBS and / or PE wax, preferably EBS and PE wax A mixed compound, wherein the mass ratio of EBS to PE wax is 1:0.5-2; the antioxidant is one or more of antioxidant 1010, antioxidant DLTP or antioxidant 168, and preferably the antioxidant is a mixed compound of antioxidant 1010, antioxidant DLTP and antioxidant 168, wherein the mass ratio of antioxidant 1010 to antioxidant DLTP is 1:0.5-2, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:0.05-0.2.

[0023] In a specific solution, when the composite material is a film material with a thickness of 25-80 μm, it has the following properties:

[0024] Tensile strength greater than 40MPA;

[0025] Yield strength greater than 15MPA;

[0026] Breaking elongation greater than 300%;

[0027] The water vapor transmission rate is less than 6 at a temperature of 38°C and a relative humidity of 100%;

[0028] The temperature is 130℃ and the thermal shrinkage is less than 8% in 30 minutes.

[0029] The composite material for cable shielding layer membrane provided by the present invention has a tensile strength greater than 40 MPA and is not easy to peel off from the metal belt; its yield strength is greater than 10 MPA, and it is not easy to be stretched and deformed during the composite process with the metal belt; the water vapor permeability is less than 6, has a good water vapor barrier effect, is not easy to be hydrolyzed, has good aging resistance, and can play a good role in protecting the metal belt within the shelf life.

[0030] In order to solve the above technical problems, the second aspect of the present invention is to provide a method for preparing the composite material for the cable shielding layer film, comprising the following steps:

[0031] S1, pre-blending magnesium hydroxide, montmorillonite, a dispersant, silicon dioxide, an antioxidant and a silane coupling agent to obtain a modified powder;

[0032] S2, granulating the modified powder of step S1 with metallocene linear low-density polyethylene, ethylene-octene copolymer, polytrifluorochloroethylene, ethylenetrifluorochloroethylene copolymer, ethylenetetrafluoroethylene copolymer and compatibilizer through a twin-screw extruder to obtain primary granulated modified particles;

[0033] S3, the modified particles obtained by the primary granulation in step S2 are granulated again by a twin-screw extruder to obtain composite material particles for cable shielding layer membrane.

[0034] In the present invention, magnesium hydroxide, montmorillonite, dispersant, silicon dioxide and silane coupling agent are pre-blended to facilitate metering of components with lower content, and the powder can be effectively coated and modified to a certain extent, while improving the dispersion uniformity; then the pre-blended modified powder is subjected to twin-screw granulation with metallocene linear low-density polyethylene, polytrifluorochloroethylene, ethylene trifluorochloroethylene copolymer, ethylene tetrafluoroethylene copolymer and compatibilizer to obtain primary granulation modified particles first. At this time, the primary granulation modified particles have poor dispersion uniformity, and direct film making may cause particles or agglomerates to appear on the film surface, affecting the performance of the film. Therefore, it is necessary to perform secondary modification granulation to finally obtain composite material particles for cable shielding layer film with excellent mechanical properties and barrier properties. The preparation method of the present invention is simple, easy to operate and convenient for industrial application.

[0035] In a specific embodiment, in step S1, pre-blending is performed in a high-speed mixer, the pre-blending speed is 100-200 rpm, the blending time is 15-25 min, and the temperature is 25-40° C.;

[0036] In step S2, the temperature of the primary granulation is 185-245°C;

[0037] In step S3, the temperature of the re-granulation is 185-245°C.

[0038] In a specific solution, in step S2, step S2 also includes drying the primary granulated modified particles, the drying temperature is 70-90° C., and the drying time is 2-8 hours.

[0039] In a specific embodiment, during the preparation process, the materials are added as follows in parts by mass:

[0040] 30-60 parts by weight of metallocene linear low-density polyethylene;

[0041] 3-10 parts by mass of ethylene-octene copolymer;

[0042] 3-20 parts by mass of polychlorotrifluoroethylene;

[0043] 3-10 parts by weight of ethylene chlorotrifluoroethylene copolymer;

[0044] 15-40 parts by weight of ethylene tetrafluoroethylene copolymer;

[0045] 3-8 parts by mass of compatibilizer;

[0046] 8-18 parts by mass of magnesium hydroxide;

[0047] 0.2-1 parts by mass of silicon dioxide;

[0048] 3-15 parts by mass of montmorillonite;

[0049] Silane coupling agent 0.3-1 parts by mass;

[0050] Dispersant 0.1-1 parts by mass;

[0051] Antioxidant 0.1-1 parts by weight.

[0052] The metallocene linear low-density polyethylene, ethylene-octene copolymer, polychlorotrifluoroethylene, ethylenechlorotrifluoroethylene copolymer and ethylenetetrafluoroethylene copolymer totaled 100 parts by mass.

[0053] In a specific embodiment, the compatibilizer is maleic anhydride grafted metallocene polyethylene;

[0054] The silane coupling agent is one or more of a triethoxysilane coupling agent and a fluorine-containing silane coupling agent;

[0055] The dispersant is EBS and / or PE wax, preferably a mixture of EBS and PE wax, wherein the mass ratio of EBS to PE wax is 1:0.5-2;

[0056] The antioxidant is one or more of antioxidant 1010, antioxidant DLTP or antioxidant 168, preferably a mixed compound of antioxidant 1010, antioxidant DLTP and antioxidant 168, wherein the mass ratio of antioxidant 1010 to antioxidant DLTP is 1:0.5-2, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:0.05-0.2.

[0057] The composite material for cable shielding layer membrane provided by the present invention has good mechanical properties such as tensile strength and yield strength, is easy to be compounded with metal tape, is not easy to be peeled off after compounding, and has good barrier properties, thus playing a good protective role for metal tape and cable; at the same time, the composite material for cable shielding layer membrane of the invention has good flame retardancy, good high temperature aging resistance, and long service life, and can play a good protective role at least within the shelf life; at the same time, the preparation method of the composite material for cable shielding layer membrane provided by the present invention is simple, easy to operate, and convenient for industrial application. DETAILED DESCRIPTION

[0058] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] The raw materials used in the examples of the present invention are all commercially available, including:

[0060] Metallocene linear low-density polyethylene: melt index 4-8g / 10min (190°C, 2.16Kg);

[0061] Ethylene-octene copolymer: melt index is 0.5-2g / 10min (190°C, 2.16Kg);

[0062] Polychlorotrifluoroethylene: Melt index range 15-25g / 10min (250℃, 2.16Kg);

[0063] Ethylene chlorotrifluoroethylene copolymer: melt index range 15-25g / 10min (250℃, 2.16Kg);

[0064] Ethylene tetrafluoroethylene copolymer: melt index is 15-25g / 10min (250℃, 2.16Kg);

[0065] Compatibilizer: maleic anhydride grafted metallocene polyethylene;

[0066] Silane coupling agent: fluorinated silane coupling agent (heptadecafluorodecyltrimethoxysilane);

[0067] Dispersant: vinyl bisstearamide and PE wax;

[0068] Antioxidants: Antioxidant 1010, Antioxidant DLTP, Antioxidant 168;

[0069] and magnesium hydroxide, silica, and montmorillonite.

[0070] The equipment in the embodiments of the present invention are all commercially available: a high-speed mixer, a twin-screw granulator and a casting extruder (specially designed for high temperature resistance and corrosion resistance).

[0071] Example 1 Preparation of composite material particles for cable shielding layer membrane

[0072] S1. Pre-blending magnesium hydroxide, montmorillonite, dispersant, silicon dioxide, antioxidant and silane coupling agent in a high-speed mixer to obtain modified powder; wherein the pre-blending speed is 100-200 rpm, the blending time is 15-25 min, and the temperature is 25-40° C.;

[0073] S2, the modified powder of step S1 is granulated with metallocene linear low-density polyethylene, ethylene-octene copolymer, polytrifluorochloroethylene, ethylenetrifluorochloroethylene copolymer, ethylenetetrafluoroethylene copolymer and compatibilizer by twin-screw extruder to obtain primary granulated modified particles; during the granulation process, the temperature is controlled between 185° C. and 245° C.; the obtained primary granulated modified particles are dried at 85° C. for 4 hours for standby use;

[0074] S3, the modified particles of the primary granulation in step S2 are granulated again by a twin-screw extruder to obtain composite material particles for cable shielding layer membrane; during the granulation process, the temperature is controlled between 185° C. and 245° C.

[0075] The addition ratio of each component in this embodiment is shown in Table 1.

[0076] Examples 2-6 and Comparative Examples 1 and 2

[0077] The preparation methods of Examples 2 to 6 and Comparative Examples 1 and 2 are the same as those of Example 1, except that the material components are different, as shown in Table 1:

[0078] Table 1

[0079]

[0080]

[0081] Embodiment 7 Performance Test

[0082] The testing method of the present invention is as follows:

[0083] The tensile strength, yield strength and elongation at break are tested according to the test method of GB / T 1040.3-2006;

[0084] The water vapor transmission rate is tested in an environment with a temperature of 38°C and a relative humidity of 100%;

[0085] Thermal shrinkage was tested at 130°C for 30 minutes;

[0086] The water contact angle is tested using a water contact angle tester;

[0087] The roughness was tested using a surface roughness tester;

[0088] Preparation of test samples: The composite material particles of Examples 1 to 6 and Comparative Examples 1 and 2 are extruded into 50 μm films (the conventional thickness of plastic films in cable shielding layer films) through a high-temperature corrosion-resistant special cast extruder, wherein the extrusion processing temperature is 190-270°C, the melt flowing out of the T-die is cooled to 130 / 110 / 90°C by a special cooling roller group, the cooled and formed film is plasma treated to obtain a film with bonding ability on the surface, and the formed film is embossed by a special roller to obtain a film with a certain surface roughness value; the samples of this embodiment are prepared according to the standards for plastic film layers in metal composite tapes, and the surface treatment of the film is to facilitate the bonding of other materials and to increase the anti-slip properties.

[0089] The film was tested, and the test results are shown in Table 2:

[0090] Table 2

[0091]

[0092] It can be seen from Table 2 that the films prepared from the composite materials obtained in Examples 1 to 6 of the present invention have greatly improved tensile strength and yield strength, low water vapor permeability, good water vapor barrier performance, and are suitable for application in cable shielding layers; the tensile rate at break of comparative example 1 is low, the tensile strength and yield strength of comparative example 2 are poor, and the water vapor permeability is also high, so it is not suitable for application in cable shielding layers.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A composite material for cable shielding layer film, characterized in that: The resin matrix includes the following components in parts by mass: 30-60 parts by weight of metallocene linear low-density polyethylene; 3-10 parts by mass of ethylene-octene copolymer; 3-20 parts by mass of polychlorotrifluoroethylene; 3-10 parts by weight of ethylene chlorotrifluoroethylene copolymer; 15-40 parts by weight of ethylene tetrafluoroethylene copolymer; The resin matrix has a total of 100 parts by mass. The composite material also includes the following components in parts by mass: 3-8 parts by mass of compatibilizer; 8-18 parts by mass of magnesium hydroxide; 0.2-1 parts by mass of silicon dioxide; 3-15 parts by mass of montmorillonite; Silane coupling agent 0.3-1 parts by mass; Dispersant 0.1-1 parts by mass; Antioxidant 0.1-1 parts by weight.

2. The composite material for cable shielding layer film according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted metallocene polyethylene; The silane coupling agent is one or more of a triethoxysilane coupling agent and a fluorine-containing silane coupling agent; The dispersant is EBS and / or PE wax; The antioxidant is one or more of antioxidant 1010 , antioxidant DLTP or antioxidant 168 .

3. The composite material for cable shielding layer film according to claim 2, characterized in that: The dispersant is a mixture of EBS and PE wax, and the mass ratio of EBS to PE wax is 1:0.5-2; The antioxidant is a mixed compound of antioxidant 1010, antioxidant DLTP and antioxidant 168, wherein the mass ratio of antioxidant 1010 to antioxidant DLTP is 1:0.5-2, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:0.05-0.

2.

4. The composite material for cable shielding layer film according to claim 1, characterized in that: When the composite material is a film material with a thickness of 25-80 μm, it has the following properties: Tensile strength greater than 40MPA; Yield strength greater than 15MPA; Breaking elongation greater than 300%; The water vapor transmission rate is less than 6 at a temperature of 38°C and a relative humidity of 100%; The temperature is 130℃ and the thermal shrinkage is less than 8% in 30 minutes.

5. A method for preparing the composite material for cable shielding layer film according to any one of claims 1 to 4, characterized in that: The steps include: S1, pre-blending magnesium hydroxide, montmorillonite, a dispersant, silicon dioxide, an antioxidant and a silane coupling agent to obtain a modified powder; S2, granulating the modified powder of step S1 with metallocene linear low-density polyethylene, ethylene-octene copolymer, polytrifluorochloroethylene, ethylenetrifluorochloroethylene copolymer, ethylenetetrafluoroethylene copolymer and compatibilizer through a twin-screw extruder to obtain primary granulated modified particles; S3, the modified particles obtained by the primary granulation in step S2 are granulated again by a twin-screw extruder to obtain composite material particles for cable shielding layer membrane.

6. The preparation method according to claim 5, characterized in that: In step S1, pre-blending is performed in a high-speed mixer, the pre-blending speed is 100-200 rpm, the blending time is 15-25 min, and the temperature is 25-40° C.; In step S2, the temperature of the primary granulation is 185-245°C; In step S3, the temperature of the re-granulation is 185-245°C.

7. The preparation method according to claim 5, characterized in that: Step S2 also includes drying the primary granulated modified particles at a drying temperature of 70-90° C. for a drying time of 2-8 hours.

8. The preparation method according to claim 5, characterized in that: In parts by mass, the materials are added as follows: 30-60 parts by weight of metallocene linear low-density polyethylene; 3-10 parts by mass of ethylene-octene copolymer; 3-20 parts by mass of polychlorotrifluoroethylene; 3-10 parts by weight of ethylene chlorotrifluoroethylene copolymer; 15-40 parts by weight of ethylene tetrafluoroethylene copolymer; 3-8 parts by mass of compatibilizer; 8-18 parts by mass of magnesium hydroxide; 0.2-1 parts by mass of silicon dioxide; 3-15 parts by mass of montmorillonite; Silane coupling agent 0.3-1 parts by mass; Dispersant 0.1-1 parts by mass; Antioxidant 0.1-1 parts by weight. The metallocene linear low-density polyethylene, ethylene-octene copolymer, polychlorotrifluoroethylene, ethylenechlorotrifluoroethylene copolymer and ethylenetetrafluoroethylene copolymer totaled 100 parts by mass.

9. The preparation method according to claim 5, characterized in that: The compatibilizer is maleic anhydride grafted metallocene polyethylene; The silane coupling agent is one or more of a triethoxysilane coupling agent and a fluorine-containing silane coupling agent; The dispersant is EBS and / or PE wax; The antioxidant is one or more of antioxidant 1010 , antioxidant DLTP or antioxidant 168 .

10. The preparation method according to claim 9, characterized in that: The dispersant is a mixture of EBS and PE wax, and the mass ratio of EBS to PE wax is 1:0.5-2; The antioxidant is a mixed compound of antioxidant 1010, antioxidant DLTP and antioxidant 168, wherein the mass ratio of antioxidant 1010 to antioxidant DLTP is 1:0.5-2, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:0.05-0.2.

Citation Information

Patent Citations

  • High-flexibility distortion-resisting robot cable

    CN105632597A

  • Halogen-free flame-retardant polyethylene cable material and preparation method thereof

    CN112280157A

  • Composite material, film and film preparation method

    CN117511046A

  • Composition for power cable sheath with high strength comprising metallocene linear low density polyethylene resin and high performance flame retardant

    KR1020120085606A

  • Highly filled unsaturated fluoropolymer compositions for cables

    US20070078209A1

Cited By

  • High-temperature-cooking-resistant packaging material and application thereof

    CN120039009A